2014
DOI: 10.1136/archdischild-2014-306423
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neonatal care in clinical training facilities in Kenya

Abstract: ObjectiveAn audit of neonatal care services provided by clinical training centres was undertaken to identify areas requiring improvement as part of wider efforts to improve newborn survival in Kenya.DesignCross-sectional study using indicators based on prior work in Kenya. Statistical analyses were descriptive with adjustment for clustering of data.SettingNeonatal units of 22 public hospitals.PatientsNeonates aged <7 days.Main outcome measuresQuality of care was assessed in terms of availability of basic resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 18 publications
5
81
0
Order By: Relevance
“…Furthermore, wider availability of pulse oximeters in facilities is essential. In 2012, only 4 of 22 Kenyan training hospitals had functional pulse oximeters 49. Oxygen provision may be improved through enhanced nurse training, including multiple ‘doses’ over time; increased numbers of neonatal nurses; and training mothers, who often participate in the care of their babies in low‐resource facilities, to titrate oxygen with supervision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, wider availability of pulse oximeters in facilities is essential. In 2012, only 4 of 22 Kenyan training hospitals had functional pulse oximeters 49. Oxygen provision may be improved through enhanced nurse training, including multiple ‘doses’ over time; increased numbers of neonatal nurses; and training mothers, who often participate in the care of their babies in low‐resource facilities, to titrate oxygen with supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen provision may be improved through enhanced nurse training, including multiple ‘doses’ over time; increased numbers of neonatal nurses; and training mothers, who often participate in the care of their babies in low‐resource facilities, to titrate oxygen with supervision. A study assessing the effects of a parent training programme for infants being discharged home on oxygen found that those who received training had significantly improved post‐test scores 49. Employment of trained care facilitators and development of simple SpO 2 monitors with algorithm‐based instructions to support mothers could also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…As the Solomon Islands embarks on efforts to improve and scale up newborn care, an understanding of the baseline quality of care is required. Previous studies assessing the quality of care for children in the Solomon Islands and neonates in other countries have illustrated the links between assessments, health policy and quality improvement activities. Information regarding gaps in standards of care, referral guidelines, infrastructure (basic equipment and medications for neonatal care) and health systems for neonatal services are essential to understand, shape and prioritise interventions.…”
mentioning
confidence: 99%
“…One option to ensure newborns access specialised care, while also limiting infection, is to expand the capacity of NBUs to appropriately accommodate older and outborn newborns. However, NBUs in public sector hospitals in Kenya currently struggle with overcrowding and high patient to nurse ratios 12 . Hence, such a policy would require strategic investment in space, including isolation rooms, and specific staff for different patient groups in many settings.…”
Section: Discussionmentioning
confidence: 99%